2017
DOI: 10.1073/pnas.1616363114
|View full text |Cite
|
Sign up to set email alerts
|

BORC/kinesin-1 ensemble drives polarized transport of lysosomes into the axon

Abstract: The ability of lysosomes to move within the cytoplasm is important for many cellular functions. This ability is particularly critical in neurons, which comprise vast, highly differentiated domains such as the axon and dendrites. The mechanisms that control lysosome movement in these domains, however, remain poorly understood. Here we show that an ensemble of BORC, Arl8, SKIP, and kinesin-1, previously shown to mediate centrifugal transport of lysosomes in nonneuronal cells, specifically drives lysosome transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
238
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(257 citation statements)
references
References 78 publications
17
238
2
Order By: Relevance
“…71.4% of MB‐positive moving puncta were co‐transported with CD63‐eGFP‐labeled vesicle‐like focal puncta, and an equal percentage of these moved anterogradely and retrogradely (Fig B–D, F and G, and Movies EV3 and EV4). This bidirectional transport is consistent with previously published studies on LE/Ly trafficking in embryonic neurons (Farías et al , ). Similar results were obtained when growth cones were cultured from older embryos (Appendix Fig S2A–G and Movie EV5).…”
Section: Resultssupporting
confidence: 93%
“…71.4% of MB‐positive moving puncta were co‐transported with CD63‐eGFP‐labeled vesicle‐like focal puncta, and an equal percentage of these moved anterogradely and retrogradely (Fig B–D, F and G, and Movies EV3 and EV4). This bidirectional transport is consistent with previously published studies on LE/Ly trafficking in embryonic neurons (Farías et al , ). Similar results were obtained when growth cones were cultured from older embryos (Appendix Fig S2A–G and Movie EV5).…”
Section: Resultssupporting
confidence: 93%
“…Lysosomes are associated with different types of MT motors (kinesin‐1, kinesin‐2, dynein) (Pu et al , ; Farias et al , ), which makes it difficult to discriminate which motor might be primarily affected by the F‐actin mesh, or if the presence of actin patches triggers competition between these motor proteins, a so‐called “tug of war”, resulting in stops and switches in transport directionality (Hancock, ). In order to be able to rule out tug‐of‐war effects, we decided to engineer a cargo that is only transported by one type of dendritic MT motor.…”
Section: Resultsmentioning
confidence: 99%
“…The GTP form of ARL8B binds to SKIP to recruit KIF5 onto the lysosomal membrane. Although a recent study has shown that this complex is essential for the axonal transport of lysosomes [35], we could not analyze the role of BORC in this phenomena in this study as mature lysosomes are largely absent in DA9 axons (Figure S1B). …”
Section: Discussionmentioning
confidence: 96%